2017
DOI: 10.1038/s41467-017-00145-y
|View full text |Cite
|
Sign up to set email alerts
|

Chronic activation of JNK JAK/STAT and oxidative stress signalling causes the loser cell status

Abstract: Cell competition is a form of cell interaction that causes the elimination of less fit cells, or losers, by wild-type (WT) cells, influencing overall tissue health. Several mutations can cause cells to become losers; however, it is not known how. Here we show that Drosophila wing disc cells carrying functionally unrelated loser mutations (Minute and mahjong) display the common activation of multiple stress signalling pathways before cell competition and find that these pathways collectively account for the los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(153 citation statements)
references
References 78 publications
(156 reference statements)
11
136
1
2
Order By: Relevance
“…Interestingly, mtDNA genes are amongst the top mis-regulated factors identified during cell competition in the mouse skin (Ellis et al, 2019). In the Drosophila wing disc oxidative stress, a general consequence of dysfunctional mitochondria, underlies the out-competition of Minute and Mah-jong mutant cells (Kucinski et al, 2017). Similarly, in Madin-Darby Canine Kidney (MDCK) cells, a loss of Δψm occurs during the out-competition of RasV12 mutant cells and is key for their extrusion (Kon et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mtDNA genes are amongst the top mis-regulated factors identified during cell competition in the mouse skin (Ellis et al, 2019). In the Drosophila wing disc oxidative stress, a general consequence of dysfunctional mitochondria, underlies the out-competition of Minute and Mah-jong mutant cells (Kucinski et al, 2017). Similarly, in Madin-Darby Canine Kidney (MDCK) cells, a loss of Δψm occurs during the out-competition of RasV12 mutant cells and is key for their extrusion (Kon et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…p53 is required to induce xrp1 upon irradiation (Akdemir et al, 2007) and was more recently shown to control growth coordination between compartments (Mesquita et al, 2010). In addition, previous work has shown that xrp1 could respond to oxidative stress (Gruenewald et al, 2009), and that both oxidative stress and Nrf2 are linked to Minute-induced cell competition (Kucinski et al, 2017). However, we find that RNAimediated downregulation of p53 or inhibition of oxidative stress signaling (UAS-CAT+SOD, UAS-nrf2 RNAi ) in slow-growing discs produces no or only minor rescue of non-autonomous growth ( Figure S2B).…”
Section: A Role For the Atypical Ribosomal Protein Rps12 In Iocmentioning
confidence: 99%
“…The genes upregulated after inactivation of the SAC also include a number encoding proteins involved in the xenobiotic response (CLEMENTE-RUIZ et al 2016). Intriguing, oxidative stress also induces many of these genes (MISRA et al 2011;KUCINSKI et al 2017), including both ones with known antioxidant roles and those, like cytochrome p450s, without known roles in this process. Another striking parallel with the data from the Ruvkun lab is the role of the JNK pathway.…”
Section: Centrosome Loss Immunity and Xenobiotic Detoxificationmentioning
confidence: 99%